ANALISIS IMPLEMENTASI KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL PERSPEKTIF TEORI PILIHAN PUBLIK DI KUTAI KARTANEGARA - Nafisah, Anis Zahrotun (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
The KTP (residence card) has undergone digitalization, with one significant change occurring in 2011, transitioning to e-KTP. The government is now introducing Digital Identity Cards (IKD) as a technological innovation. IKD replaces physical KTP cards with electronic versions that can be stored on devices like smartphones. This study aims to analyze the implementation of the IKD policy from the perspective of Public Choice Theory at the Department of Population and Civil Registration in Kutai Kartanegara Regency, evaluating public interests and potential bureaucratic personal gains. The research employs an exploratory qualitative approach to assess the benefits and rationale behind the policy, with key informant Muhammad Iryanto, the Head of the Department. Snowball sampling is used to determine sources, while data is collected through observation, in-depth interviews, questionnaires, and documentation. Data analysis follows the Miles, Huberman, and Saldana method, including data reduction, data display, and conclusion drawing/verification. The study's findings indicate: 1) IKD is more driven by central government interests than public interests, 2) IKD negatively impacts the budget due to the double-track policy, and 3) The government aims to showcase technological advancements in services, though the benefits are less optimal for the Kutai Kartanegara region, primarily serving to enhance bureaucratic image in the public eye.